(untitled) (LIS TODAY, 2025)
This study examines research trends on quality education in India from 2005 to 2024 through bibliometric analysis, addressing the lack of a comprehensive understanding of Indian research output in this critical area. Key aspects analyzed include publication trends, leading authors, thematic areas, influential institutions, and prominent sources. Data extracted from the Scopus database on November 22, 2024, yielded 654 publications, analyzed using MS Excel and Bibliometrix R software. Findings reveal a notable rise in publications, especially post-2020, with peaks in 2023 and 2024. Authors like Raghu Raman and Priyadarshini Dey, along with institutions such as the University of Delhi and Christ University, emerged as significant contributors. Dominant themes include social sciences, computer science, and engineering, while popular keywords such as “quality education” and “e-learning” reflect emerging trends. The study offers actionable insights for policymakers, educators, and researchers to enhance collaborations, address research gaps, and support sustainable educational development.